2009
DOI: 10.1093/cvr/cvp194
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic mechanism for initiation of rapid firing from atria and pulmonary veins: evidence by ablation of ganglionated plexi

Abstract: HFS applied to local atrial and PV sites initiated rapid firing via activation of the interactive autonomic network in the heart. GP in either left side or right side contributes to the rapid firings and AF originating from ipsolateral and contralateral PVs and atrium. Autonomic denervation suppresses or eliminates those rapid firings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 22 publications
1
89
0
1
Order By: Relevance
“…81,84,85 Animal studies have demonstrated that stimulation of GP located around the pulmonary veins can reduce the number of atrial extrastimuli required to initiate AF, and that neuronal/autonomic blockade with drugs or GP ablation can prevent AF induction. 86,87 Because GP are located near the pulmonary veins, conventional PVI can often coincidently eliminate these areas, and it has been suggested that ablation of GP may help explain the success of PVI. In an early study, Pappone and colleagues assessed for vagal responses (bradycardia, hypotension, heart block or asystole) which occurred within a few seconds after the onset of ablation.…”
Section: The Influence Of the Autonomic Nervous System And Ganglionatmentioning
confidence: 99%
“…81,84,85 Animal studies have demonstrated that stimulation of GP located around the pulmonary veins can reduce the number of atrial extrastimuli required to initiate AF, and that neuronal/autonomic blockade with drugs or GP ablation can prevent AF induction. 86,87 Because GP are located near the pulmonary veins, conventional PVI can often coincidently eliminate these areas, and it has been suggested that ablation of GP may help explain the success of PVI. In an early study, Pappone and colleagues assessed for vagal responses (bradycardia, hypotension, heart block or asystole) which occurred within a few seconds after the onset of ablation.…”
Section: The Influence Of the Autonomic Nervous System And Ganglionatmentioning
confidence: 99%
“…A comparatively dense network of nerve endings is found particularly at the insertion the pulmonary veins in the left atrium, where it is associated with the development of atrial fibrillation [10]. In addition to the electrical isolation of the pulmonary vein opening from the atrial myocardium, initial clinical data indicate that the targeted ablation of autonomic ganglia could also exert an antiarrhythmic effect [11]. However, the identification of suitable epicardial ganglions and their selective ablation is technically sophisticated and currently has only limited clinical application.…”
Section: Intrinsic Systemmentioning
confidence: 99%
“…Multiple tiers of neuronal processing occur within the cardiac neuronal hierarchy that ultimately acts to coordinate neuronal inputs to the heart (4, 7, 13). Stresses, either pathological or physiological, may disrupt the balance of efferent neuronal inputs that can lead to altered cardiac function (6,22). As such, novel therapies that overcome any such imbalance in cardiac control, as represented by neuromodulation of the ICN via SCS, may moderate excessive activation of the ICN in response to transduction of pathological cardiac stressors.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…EXCESSIVE ACTIVATION OF SELECT inputs to the intrinsic cardiac nervous system (ICN) are known to elicit atrial arrhythmias in normal (9,22,28) and pathophysiological states (11,30). Discrete activation of the axons in select mediastinal nerves can reproducibly elicit self-terminating periods of atrial tachyarrhythmias/fibrillation (ATF) (9).…”
mentioning
confidence: 99%